Content Analysis of English Textbook for Eleventh Graders Based on Merdeka Curriculum at SMA Negeri 1 Pracimantoro - Fatimah, Utami Nur; Budiharso, Teguh; Giyoto (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study analyzes the "Pathway to English" textbook for Eleventh graders, which is designed in accordance with the Merdeka Curriculum at SMA Negeri 1 Pracimantoro. Using a qualitative descriptive approach and content analysis, data were collected through observations, interviews with teachers, and document analysis. The research aimed to evaluate the textbook's alignment with BSKAP standards, focusing on content, presentation, design, and graphic quality. The findings indicate that the textbook aligns with the Merdeka Curriculum by promoting critical thinking and real-world applications. However, some weaknesses were identified, such as overly broad material, reliance on digital resources, and black-and-white illustrations, which may hinder student engagement. Recommendations for improvement include refining content focus, reducing technological dependency, and enhancing visual appeal.